Celebrating Adam Watkins' Fifth Birthday at Home - Watkins, Howard::::::::: (1983)
Adam Watkins in pajamas opening birthday presents; yellow Kermit the Frog lunchbox Cassette-AM/FM portable radio; crib in dining room